2017
DOI: 10.26719/2017.23.2.73
|View full text |Cite
|
Sign up to set email alerts
|

Dentists' perception of primary health care services in family health and mother and child health clinics in Alexandria, Egypt

Abstract: This study compared dentists' perceptions of provided services in Family Health (FH) and Mother and Child Health (MCH) clinics. A questionnaire was distributed to 120 dentists in 7 FH and 4 MCH clinics in Alexandria, Egypt in 2012. The questionnaire assessed personal and professional background, perceptions of primary health care (PHC) role, types of services provided, patient recall and referral systems and perception of service quality. The response rate was 100%. More FH dentists perceived their role to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…It includes dental care provided through the family health model (34). Previous research showed that dentists working in family health clinics expressed concerns about the availability and affordability of services to patients (35). If the new law can reduce the financial burden to patients, and the accompanying restructuring of the healthcare system provides adequate financial incentives to dentists, the economic constraints affecting the shortage of dentists may be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…It includes dental care provided through the family health model (34). Previous research showed that dentists working in family health clinics expressed concerns about the availability and affordability of services to patients (35). If the new law can reduce the financial burden to patients, and the accompanying restructuring of the healthcare system provides adequate financial incentives to dentists, the economic constraints affecting the shortage of dentists may be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the malpractice that is accepted as an option of traditional treatment for sick children in African countries. [3][4][5] A study conducted in 36 African ethnic groups showed that (2.1%) of patients were missing one or more canines. The burden was higher in East African countries, of which, 20.8% experienced teeth loss due to primary teeth extraction.…”
Section: Introductionmentioning
confidence: 99%